The Effect Of Workload On The Work Productivity Of Nurses At Pemangkat Regional General Hospital Sambas Regency - Dede Suherman; Indriati Paskarini (Universitas Tribhuwana Tunggadewi, 2025)
Workload is one of the critical factors influencing nurses’ productivity in hospital settings. Excessive workload may lead to fatigue, stress, and decreased concentration, ultimately compromising service quality and patient safety. At Pemangkat Regional General Hospital, Sambas Regency, the imbalance between the number of nurses and patients, combined with limited resources, contributes to increased workload and reduced productivity. This study aims to analyze the effect of workload on the work productivity of nurses. This study employed a quantitative approach with a cross-sectional design. A total of 172 nurses were selected through simple random sampling. The workload variable was measured using the Copenhagen Psychosocial Questionnaire III (COPSOQ III), while work productivity was measured using the Indonesian version of the Individual Work Performance Questionnaire (IWPQ). Primary data were collected through self-administered questionnaires, and data analysis was performed using IBM SPSS Statistics version 25. Statistical tests included univariate, bivariate, and multivariate analyses with a 95% confidence level. The Chi-Square test was used to examine the relationship between variables, and linear regression analysis was conducted to determine the influence of workload on productivity. The findings showed that 59.3% of nurses experienced a high workload, and 51.7% were categorized as unproductive. Statistical analysis indicated a significant relationship between workload and nurse productivity (p = 0.011). The Prevalence Ratio (PR) value of 2.232 (95% CI: 1.200–4.152) revealed that nurses with high workloads are 2.2 times more likely to be unproductive than those with lower workloads. High workload negatively affects nurses’ performance by increasing fatigue, psychological strain, and reducing motivation. Effective workload management through adequate staffing, equitable scheduling, and supportive leadership are crucial to maintain nurses’ well-being and optimize productivity. Workload has a significant affects nurse productivity at Pemangkat Regional General Hospital. Implementing workload control strategies is recommended to sustain productivity and service quality.